Curriculum Management of Al Izzah Islamic International Boarding School Batu - Anwar Sa'dullah; Abdul Haris; Wahidmurni Wahidmurni (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
Curriculum management is a basic component in the world of Islamic education. if it is developed through a good management system, it will become the basis of competitive advantage in the era of the industrial revolution 4.0. Islamic education, especially Islamic boarding schools will face the challenge of competition in providing educational services and will not be avoided, this happens because of the development of globalization of technology and information. Curriculum management will be a strategic component in responding to these global challenges.